2019
DOI: 10.1177/0300985818825128
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Validation of a Whole-Slide Imaging Scanner in Cytological Samples: Diagnostic Accuracy and Comparison With Light Microscopy

Abstract: Digital slides created by whole-slide imaging scanners can be evaluated by pathologists located in remote sites, but the process must be validated before this technology can be applied to routine cytological diagnosis. The aim of this study was to validate a whole-slide imaging scanner for cytological samples. Sixty cytological samples, whose diagnoses were confirmed by gold-standard examinations (histology or flow cytometry), were digitalized using a whole-slide imaging scanner. Digital slides and glass slide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…There is generally good agreement between WSI and light microscopy (LM) with regard to cytologic and histologic diagnosis and MC in animal and human tumors. 2,3,13,16,18,29,32,48,53,64 A better correlation was observed in cases with higher MCs as compared to those with lower MCs. 3 Some studies reported a trend toward underestimating the MC with WSI as compared to LM and attributed this to difficulty of identifying MF via WSI.…”
Section: Wsi Validation For Diagnosis and MCmentioning
confidence: 86%
“…There is generally good agreement between WSI and light microscopy (LM) with regard to cytologic and histologic diagnosis and MC in animal and human tumors. 2,3,13,16,18,29,32,48,53,64 A better correlation was observed in cases with higher MCs as compared to those with lower MCs. 3 Some studies reported a trend toward underestimating the MC with WSI as compared to LM and attributed this to difficulty of identifying MF via WSI.…”
Section: Wsi Validation For Diagnosis and MCmentioning
confidence: 86%
“…43 For specific diagnostic tasks, such as identification of neoplastic processes, true positive (TP), true negative (TN), false positive (FP), and false negative (FN) can be defined and used for calculation of sensitivity . 20 A true gold standard, however, may not be available for all diagnostic pathology tasks. For example, a cytologic validation study may use histologic diagnoses or flow cytometric diagnoses (for lymphoid tumors) as a gold standard.…”
Section: Simple Modality Comparison Studiesmentioning
confidence: 99%
“…For example, a cytologic validation study may use histologic diagnoses or flow cytometric diagnoses (for lymphoid tumors) as a gold standard. 20,21 Although histologic and cytologic specimens may not always allow the same interpretation, histology is independent to cytology (as it is not used by the study pathologists) and is generally considered superior ("true" diagnosis) for most disease entities (there are some exceptions). Therefore, it may be used as a gold standard (GS) method to determine "equivalency" or "superiority" (as opposed to agreement or concordance) between DM and LM.…”
Section: Simple Modality Comparison Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Similar rates were identified for cases evaluating veterinary samples. 1,26 The overall interpretation is that diagnoses made using whole slide images emulated those made by conventional light microscopy.…”
Section: Previous Experience In Veterinary and Human Medical Pathologymentioning
confidence: 99%